POTENSI PENGEMBANGAN PETERNAKAN SAPI POTONG TERHADAP PENYAKIT MULUT DAN KUKU (PMK) DI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Noorrahman, Nabil Fariz; Sandriya, Ardi; Arief, Fahmi (VITEK : Bidang Kedokteran Hewan, 2025)
Abstract Tanah Laut Regency in South Kalimantan holds strong potential in the beef cattle sector. However, Foot and Mouth Disease (FMD) has negatively impacted livestock productivity and farmers’ incomes in Indonesia. This study aims to assess the impact of FMD on beef cattle farming and identify sustainable development strategies. A descriptive survey approach was used, combining quantitative and qualitative methods. Data were collected through field observations, farmer interviews, and secondary sources from the Department of Livestock and Animal Health in Tanah Laut. Analysis showed a high morbidity rate (60–75%) and low mortality (<5%). FMD reduced feed intake, weight gain, and caused marketing disruptions due to movement restrictions. Most farmers use traditional or semi-intensive systems with low biosecurity, increasing disease transmission risk. Control efforts like vaccination, quarantine, and biosecurity campaigns are ongoing but hindered by vaccine distribution and limited awareness. Sustainable strategies are urgently needed, including optimized vaccination, feed diversification, farmer group institutional strengthening, and adoption of modern livestock technologies. In conclusion, FMD presents a major challenge to beef cattle development in Tanah Laut Regency. Strong collaboration among government, academia, and farmers is crucial to build resilience and enhance the sector’s competitiveness amid disease threats.